KAJIAN ETNOBOTANI TANAMAN Curcuma longa L. DAN Curcuma zanthorrhiza ROXB. OLEH MASYARAKAT BOGOR JAWA - Malia Ulfah; Wardah Wardah; Rusmadi Rusmadi; Muhammad A'tourrohman (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The community of Bogor, West Java are a group of people who still apply the traditional pattern of life. The use of turmeric plants (Curcuma longa L.) and temu lawak (Curcuma zanthorrhiza Roxb.) by local people is still ongoing today. This research was conducted to determine the economic value of turmeric and temulawak for the people of Bogor, the use and use of turmeric and temu lawak plants, and the role of ethnobotany for the development of science. The method used in this study is data collection techniques in the form of literature studies, observations, interviews, and documentation. The results show that turmeric and temu lawak have economic potential for the people of Bogor, West Java. Its uses include medicinal plants, food additives and as vegetables. How to use it is to be mashed, cut and consumed directly. Revitalizing community knowledge about the use of plants around is very important for the development of science.